KARAKTERISTIK AIR TANAH DI SEKITAR RAWA JOMBOR, KLATEN DAN POTENSINYA SEBAGAI SUMBER BELAJAR GEOGRAFI DI LAPANGAN - Indrayati, Ariyani; Setyaningsih, Wahyu (Universitas Negeri Semarang, 2016)
The groundwater characteristic at Rawa Jombor and surrounding area are very unique. There are aquiferstratified that produce three kinds of water: fresh, marsh, and salty. It’s very interesting to conduct researchfurthermore, about distribution, how is the occurrence, and how potential as geography learning resource in thefield. The research method are quantitative, data gets by measure the physical and chemical properties ofgroundwater. Next step are data analisys: by mapping to understand the distribution, occurance analize to knowthe genesis, and the last step is cross-classification to measure the potential as a learning resource, in suitabilityand relevance to the competence of geography graduates. Based on the physical (salinity) and chemical(electrical conductivity) properties of groundwater measurement, we sure that there are three kinds of water:fresh, marsh, and salty. Most of he aquifer that produce fresh water occurance in the northern swamp (RawaJombor). The genesis is because of this area formed from Merapi vulcan material. Most of he aquifer thatproduce salty water occurance in the southern swamp (Rawa Jombor). The genesis is because of this area formedfrom sea sedimentation that upraised. The marsh water is found at the border of both area. Based on crossclassificationbetween the research object and the standard variabel is known that Rawa Jombor and surroundingarea are suitable and relevance use as learning resource, to support geography competence graduate.